Modulation of Adenylyl Cyclase Activity in Rat Striatal Homogenate by Dopaminergic Receptors - Argo Vonk; Reet Reinart; Ago Rinken (Elsevier, 2008)
We have characterized the modulation of adenylyl cyclase (AC) activity by ligands of dopaminergic receptors in rat striatal homogenate and compared the results with receptor-ligand binding affinities. Despite the fact that rat striatum contains high level of both dopamine D1 and D2 receptors, only the D1-specific AC activation by agonists could be determined. All D1-receptor agonists (dopamine, dihydrexidine, and A 77636) used were able to increase cAMP accumulation in a concentration-dependent manner, while D1-receptor antagonists (SCH23390, SKF83566, and butaclamol) blocked the effects induced by the aforementioned agonists. At the same time, the D2-receptor agonist quinpirole and antagonist sulpiride had no effect on cAMP accumulation in striatal homogenate neither on the basal level nor on the activated level of AC, while inhibited [3H]raclopride binding to these membranes. Comparing the ligands of the D1 receptor in modulating the activity of AC and displacing D1-receptor-specific radioligand [3H]SCH23390 binding revealed that the ligands modulate both of these processes with similar affinities. It indicates that under given experimental conditions, only dopamine D1-receptor-mediated stimulation of AC activity can be measured in membrane homogenate of rat striatum, while dopamine D2-receptor effects remain fully hidden. Keywords:: adenylyl cyclase, cAMP, dopamine D1 receptor, subtype selective assay, rat striatum